(untitled) (Academicia Globe: Inderscience Research, 2023)
This article analyzes the activity of the bond market in foreign countries, particularly the USA, Germany, Japan, and China, as well as the types of securities and their purchase and sale processes based on foreign legislation. Also, in the article, the types of bonds used in the stock exchange of Uzbekistan and in the activities of banks and their behavior are compared with the practice of foreign countries.